The genome and transcriptome of Sarocladium terricola provide insight into ergosterol biosynthesis - Wang, Wei; Nie, Yong; Liu, Xiao-Yong; Huang, Bo (Frontiers in Cellular and Infection Microbiology, 2023)
Sarocladium terricola is a species of ascomycete fungus that has been recognized as a biocontrol agent for managing animal and plant pathogens, and exhibits significant potential as a feed additive. In this study, we utilized a combination of short-read Illumina sequencing and long-read PacBio sequencing to sequence, assemble, and analyze the genome of S. terricola. The resulting genome consisted of 11 scaffolds encompassing 30.27 Mb, with a GC content of 54.07%, and 10,326 predicted protein coding gene models. We utilized 268 single-copy ortholog genes to reconstruct the phylogenomic relationships among 26 ascomycetes, and found that S. terricola was closely related to two Acremonium species. We also determined that the ergosterol content of S. terricola was synthesized to nearly double levels when cultured in potato dextrose media compared to bean media (4509 mg/kg vs. 2382 mg/kg). Furthermore, transcriptome analyses of differentially expressed genes suggested that the ergosterol synthesis genes ERG3, ERG5, and ERG25 were significantly up-regulated in potato dextrose media.